IMPROVEMENT OF TEACHING THE TOPIC “BEGINNING TO WORK WITH ELECTRONIC MAIL” BASED ON SOFTWARE TOOLS (Multidisciplinary Journal of Science and Technology, 2024)
This article discusses the issues of creating multimedia presentations based on modern software tools and organizing lessons using them in teaching the topic “Getting Started with Email” in the 5th grade of “Informatics and Information Technologies” subject in general secondary schools today.